Slade house ebook A novel. - Mitchell, David (2015)
The New York Times bestseller by the author of The Bone Clocks and Cloud Atlas |  Named One of the Best Books of the Year by San Francisco Chronicle,  NPR, Los Angeles Times, The Guardian, The Telegraph, National Post, BookPage, and  Kirkus Reviews Keep your eyes peeled for a small black iron door. Down the road from a working-class British pub, along the brick wall of a narrow alley, if the conditions are exactly right, you’ll find the entrance to Slade House. A stranger will greet you by name and invite you inside. At first, you won’t want to leave. Later, you’ll find that you can’t. Every nine years, the house’s residents—an odd brother and sister—extend a unique invitation to someone who’s different or lonely: a precocious teenager, a recently divorced policeman, a shy college student. But what really goes on inside Slade House? For those who find out, it’s already too late. . . . Spanning five decades, from the last days of the 1970s to the present, leaping genres, and barreling toward an astonishing conclusion, this intricately woven novel will pull you into a reality-warping new vision of the haunted house story—as only David Mitchell could imagine it. Praise for Slade House “A fiendish delight . . . Mitchell is something of a magician.” — The Washington Post “Entertainingly eerie . . . We turn to [Mitchell] for brain-tickling puzzle palaces, for character studies and for language.” — Chicago Tribune “A ripping yarn . . . Like Shirley Jackson’s Hill House or the Overlook Hotel from Stephen King’s The Shining, [Slade House] is a thin sliver of hell designed to entrap the unwary. . . . As the Mitchellverse grows ever more expansive and connected, this short but powerful novel hints at still more marvels to come.” — San Francisco Chronicle “Like Stephen King in a fever . . . manically ingenious.” — The Guardian (U.K.) “A haunted house story that savors of Dickens, Stephen King, J. K. Rowling and H. P. Lovecraft, but possesses more psychic voltage than any of them.” — Pittsburgh Post-Gazette “Tightly crafted and suspenseful yet warmly human . . . the ultimate spooky nursery tale for adults.” — The Huffington Post